Foot Massage for Improving Sleep Quality in Hemodialysis Patients: A Case Study - Laela Nur Nabilah; Kusuma, Henni; Hidayati, Wahyu; Le-Trinh Lam (Journal of Health Sciences, 2026)
Sleep disorders are a common and significant issue among haemodialysis (HD) patients, often leading to a decline in their quality of life. Foot massage is one of the nonpharmacological therapies that could be effective in managing sleep disorders among patients with hemodialysis. This study aimed to evaluate the effectiveness of foot massage in improving sleep quality in HD patients. A case study was conducted involving three HD patients with poor sleep quality at the Haemodialysis Unit of Dr. Kariadi General Hospital, Semarang, in May 2025. The Pittsburgh Sleep Quality Index (PSQI) was used to assess sleep quality before and after the intervention. Foot massage was performed for 10 minutes during dialysis sessions, twice weekly for four consecutive weeks. The results showed decreased PSQI scores after the intervention in three patients, indicating improved sleep quality. These findings suggest that foot massage positively affects sleep quality in haemodialysis patients and can be considered a beneficial nonpharmacological intervention in nursing practice.